Lithium Salt Screening for PEO-Based Solid Electrolytes of All Solid-State Li Ion Batteries Using Density Functional Theory - Qian Liu; Jinghua Yin; Minghua Chen; Jialong Shen; Xinhao Zhao; Yulong Liu (Crystals)
As key components in solid-state electrolytes, lithium salts influence the electrochemical window, ionic conductivity, and ultimately the full battery’s performance. To reduce the selection time and costs while providing electric and molecular level insights into the interactions of elements and components in solid polymer electrolytes, this paper proposes a rapid screening method based on Density Functional Theory (DFT). The structure stability, electrochemical stability, and ionic conductivity of eight common inorganic and organic lithium salts were systematically investigated by analyzing five parameters: formation energy, band gap, Li+–anion dissociation energy, anion–PEO binding energy, and anion diffusion barriers along PEO chains. Through a comprehensive analysis of these parameters obtained from DFT, LiTFSI has been identified as the most suitable lithium salt. The electrolytes fabricated by LiTFSI exhibited better performance. This approach, characterized by its rapidness, efficiency, and low cost, provides a viable method for screening lithium salts in developing solid-state batteries.